Growth hormone gene polymorphism associated with grow-out performance of Oreochromis niloticus strains - Dessimoni Dias, Marco Aurelio; Reis Neto, Rafael Vilhena [UNESP]; Sousa Bueno Filho, Julio Silvio de; Khalil Jaser, Suhaila Karim; Lago, Aline de Assis; Silva Hilsdorf, Alexandre Wagner (Elsevier B.V., 2019)
Introgressive crossbreeding between Red-Stirling and Chitralada Nile tilapia was carried out to assess the association of polymorphisms of short tandem repeats loci located in the growth hormone-I promoter and first intron with growth performance. The growth of seven genetic groups was assessed using a mixed linear model. We considered sex, age, and initial weight class of each animal as fixed effects, while genetic group, and polymorphisms in the short tandem repeats in the promoter and in the intron were considered as random effects. We found six alleles in the promoter, which were arranged in 18 of the 21 genotypic possible combinations. Alleles 191 and 196 of the promoter correspond to 80% of the assessed individuals' total alleles, and genotypes 196/196, 191/196 and 196/201 were the most frequent. We found only three alleles in the intron. Allelic variation at the promoter locus showed a significant association with weight, genotypes 181/181, 181/191 and 196/206 showed higher average weight, and genotypes 196/201, 201/201 and 191/196 showed the lowest weight. The polymorphism in the intron was not associated with fish weight. The approach utilized is unprecedented for short tandem repeats found in the growth hormone-I gene. The observed association indicates that this gene's polymorphism could be used as a tool in tilapia breeding programs.
Keywords: STR; Nile tilapia; GH; promoter; Intron